A war of words. The representation of the war in Ukraine in the sports media of Latvia - Anastasija Ropa (Eracle, 2023)
Latvia is an ex-Soviet country with Latvian and ethnically Russian population and a history of uneasy relationship with Russia, including the love and hate relationship with Russian sports. Many athletes and trainers working in Latvia have competed and were trained in Russia, using Russian facilities, or, for the older generation, the Soviet Union. However, Russia and Russian-speaking Latvian residents, including the citizens of Latvia, have been long viewed with suspicion and have been the subject of discrimination at times of crisis. This paper examines the representation of the war in Ukraine in the sporting media of Latvia from February to early October 2022. The material is sourced from the main news portal of Latvia, Delfi, which has a Latvian-language and a Russian-language versions. It is found that the two versions have significant differences in the way they refer to the war in sport-related news items.